PENGARUH KEPADATAN PENDUDUK, INDEKS PEMBANGUNAN MANUSIA, PEMBERDAYAAN GENDER, DAN KEMAHALAN KONSTRUKSI TERHADAP PERTUMBUHAN EKONOMI PROVINSI LAMPUNG TAHUN 2020–2024 - Dewi, Kirana; Yunarti, Yuyun; Nisa, Thoyibatun (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
This study seeks to examine the impact of population density, Human Development Index (HDI), Gender Empowerment Index, and Construction Cost Index (CCI) on economic growth in the districts and cities of Lampung Province. The employed study methodology is a quantitative technique using secondary panel data obtained from the Central Statistics Agency, encompassing 15 districts/cities for the period from 2020 to 2024. The employed analytical method is panel data regression, using the Chow test and the Hausman test to determine the optimal model, which indicates that the Fixed Effect Model (FEM) is the most suitable choice. The FEM estimation results indicate that HDI and IKK exert a positive and considerable influence on economic growth, however population density and IDG do not demonstrate a significant impact. These findings indicate that improving human resource quality and physical development dynamics through the construction sector are the main factors driving regional economic growth in Lampung Province, while demographic and social factors such as population density and gender empowerment have not been able to contribute directly to economic growth during the observation period.